THE EFFECTIVENESS OF THE LAW ENFORCEMENT OF HEALTH PROTOCOLS IN EFFORTS TO PREVENT AND CONTROL COVID-19 BY SATPOL PP, BANDUNG CITY - Tira Andhika Handayani; Wawan Kurniawan (International Journal of Latin Notary, 2021)
SARS-CoV-2 or better known as the Corona Virus is the virus that causes the Covid-19 pandemic. In several countries, including Indonesia, the problem of handling the spread of the corona virus pandemic (Covid-19) continues to be carried out. Since August 2020, the Regional Government of Bandung City has effectively implemented Bandung City Regulation Number 37 of 2020 concerning Guidelines for Adaptation of New Habits in the Context of Prevention and Control of Corona Virus Disease 2019. As a leading sector in suppressing the level of spread of the virus, the Bandung City Satpol PP has carried out . One of the efforts made by the Satpol PP as the implementer of the Bandung City government policy is by making several efforts ranging from socialization, appeals to enforcement. The Satpol PP, assisted by the joint apparatus of the National Police and the National Police, enforces restrictions in several areas that have the potential to accumulate masses at one point, such as areas that are densely populated with street vendors, cafes, parks etc. Law enforcement carried out by the Satpol PP is solely carried out to provide an understanding of the citizens of the importance of maintaining personal health and the environment during the current pandemic. The enactment of the Bandung mayor Regulation, Number 37 of 2020 concerning Guidelines for Adaptation of New Habits in the Context of Prevention and Control of Corona Virus Disease 2019. The number of people exposed to not using a mask is still a lot. The effectiveness of implementing health protocols becomes a question when the level of spread and the level of violations of health protocols is still relatively high.